2001
DOI: 10.1163/156855501744810
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins in polymer synthesis: photocrosslinkable films via free radical copolymerization of methylated β-cyclodextrin-complexed styrene with sodium 4-(acrylamido)-phenyldiazosulfonate in aqueous medium

Abstract: Abstract-The copolymerization of a methylated-¯-cyclodextrin (m-¯-CD) 1 : 1 host-guest compound of styrene (1a) with various molar ratios of sodium 4-(acrylamido)-phenyldiazosulfonate (2) is described. The copolymerization of complex 1a with 2 was carried out in water with 2,2 0 -azobis-(N,N 0 -dimethyleneisobutyramidine)-dihydrochloride as the free radical initiator at 40 ± C. Depending on the amount of 2 incorporated in the copolymer, water-or DMF-soluble copolymers of high molar mass were obtained. Irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…[1,2] For these reasons our group is focused on the use of cyclodextrins in polymer chemistry, a field that has recently received a great deal of industrial attention. [3][4][5][6][7][8][9][10][11][12][13][14] Cyclodextrins (CD) are cyclic oligomers of amylose consisting of six, seven or eight glucose units (a-, b-, g-cyclodextrin, respectively). The cyclodextrin molecules resemble a hollow truncated cone, with primary hydroxy groups at the narrower end and secondary hydroxy groups at the broader end.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] For these reasons our group is focused on the use of cyclodextrins in polymer chemistry, a field that has recently received a great deal of industrial attention. [3][4][5][6][7][8][9][10][11][12][13][14] Cyclodextrins (CD) are cyclic oligomers of amylose consisting of six, seven or eight glucose units (a-, b-, g-cyclodextrin, respectively). The cyclodextrin molecules resemble a hollow truncated cone, with primary hydroxy groups at the narrower end and secondary hydroxy groups at the broader end.…”
Section: Introductionmentioning
confidence: 99%
“…This methylated b-CD, which is also used in consumer products, is synthesized industrially on a large scale and is therefore readily available. [15] We have recently investigated the free-radical [3][4][5][6][7][8][9][10][11][12][13][14] and controlled-''living'' [16] polymerizations of various CDcomplexed vinyl derivatives and also some other types of monomers under surfactant-free conditions. For example, the synthesis of conducting polymers under oxidative conditions [11,17] from aqueous media was described.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in our group, the radical polymerization in aqueous solution of some hydrophobic monomers that were solubilized by complexation with methylated-b-CD was investigated and it was shown that higher monomer conversions were obtained as compared with the radical polymerization of uncomplexed monomers. [4][5][6][7][8] This concept has been also applied, for example, to the free-radical copolymerization of a water-soluble monomer (sodium 4-(acrylamido)-phenyldiazosulfonate) [9] or N-isopropylacrylamide) [10] with styrene, in aqueous solution using CD as solubilizer. Recently, the cross-linking reaction in a homogeneous aqueous medium of a watersoluble unsaturated polyester by use of a styrene/methylated-b-CD complex was reported.…”
Section: Introductionmentioning
confidence: 99%
“…In almost all examples studied before, water insoluble polymers were obtained in a high yield. [8][9][10][11][12][13][14][15][16][17][18] It was demonstrated that, generally during the propagation steps, the CD-host slips off from the monomer and the resulting polymer precipitates. Because of the high water solubility of the methylated CDs this component remains in solution.…”
Section: Introductionmentioning
confidence: 99%
“…One of several potential applications of this method is the possibility to copolymerize water soluble and completely water insoluble monomers via formation of CD-complexes. [18] We normally found that the polymerization rate of the complexed hydrophobic monomers is increased by the CD-host because of a drastic increase of concentration of the molecularly dispersed monomer complexes in the water phase.…”
Section: Introductionmentioning
confidence: 99%